Reversible cross-linked 3d ring articles and methods

By using crosslinking compositions formed by ethylene polymers and BiTEMPS methacrylate, a high heat resistance and recyclable 3DRLM material was prepared, which solved the problems of insufficient heat resistance and non-recyclable existing materials, and was suitable for high-temperature transportation applications.

CN119546650APending Publication Date: 2025-02-28DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052917.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The heat resistance of existing polyolefin solutions is insufficient for certain transportation applications, and conventional crosslinked 3DL liner materials cannot be recycled via melt processing.

Method used

A three-dimensional random ring material (3DRLM) was prepared using a crosslinking composition formed of ethylene polymer and 2,2,6,6-tetramethyl-4-piperidyl methacrylate disulfide (BiTEMPS) methacrylate, which is melt-bonded at multiple contact points to form multiple rings, which has high heat resistance and can be recycled by melt processing.

Benefits of technology

A high heat resistance and recyclable 3DRLM material is achieved, suitable for transportation applications where compression and permanent deformation are permanently deformed at high temperatures while maintaining the processability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546650A_ABST
    Figure CN119546650A_ABST
Patent Text Reader

Abstract

The present disclosure provides an article of manufacture. In one embodiment, the article is a three-dimensional random loop material ("3DRLM") composed of a mesh structure of a plurality of curved continuous wires melt bonded together at a plurality of contact points to form a plurality of loops. Each continuous wire is composed of a cross-linking composition formed from a starting material comprising (i) an ethylene-based polymer and (ii) a 2, 2, 6, 6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). This results in a 3DRLM consisting of a crosslinked composition comprising (i) an ethylene-based polymer and (ii) a bond (I) # imgabs0 # having the following structure (2).
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Three-dimensional loop ("3DL") cushions made from thermoplastic resins have been developed for applications such as automotive seating and consumer mattresses. 3DL cushions made from thermoplastic resins have become a viable alternative to thermoset polyurethane foams. Since 3DL cushions are made from thermoplastic resins, these 3DL structures can be recycled via melt processing. Polyolefins with densities ranging from 0.860 g / cc to 0.925 g / cc and melt indices (MI) ranging from 0.5 g / 10 min to 30 g / 10 min in viscosity have been demonstrated to be useful for producing 3D loop cushions with a good balance of properties.

[0002] For certain 3DL cushioning applications, and in particular 3DL cushioning transportation applications (including automobiles, trains, buses), the cushioning products require high heat resistance (compression set at high temperatures). The heat resistance of existing polyolefin solutions is insufficient for certain transportation applications. Although cross-linking can be used to improve the heat resistance of these articles, conventional cross-linked 3DL cushioning materials cannot be recycled via melt processing. Therefore, the art recognizes the need for 3DL cushioning materials that have (i) high heat resistance and (ii) can be recycled via melt processing. Summary of the invention

[0003] The present disclosure provides an article. In one embodiment, the article is a three-dimensional random ring material ("3DRLM"), which is composed of a network structure of multiple curved continuous wires melt-bonded together at multiple contact points to form multiple rings. Each continuous wire is composed of a cross-linked composition, which is formed by a starting material comprising (i) an ethylene polymer and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). This produces a 3DRLM composed of a cross-linked composition, which comprises (i) an ethylene polymer and (ii) a bond having the following structure (2):

[0004]

[0005] The present disclosure provides a method. In one embodiment, the method includes heating a first article to a reprocessing temperature, the first article consisting of a three-dimensional random ring material, the three-dimensional random ring material comprising a network structure of a plurality of curved continuous wires melt-bonded together at a plurality of contact points to form a plurality of rings, each continuous wire consisting of a cross-linked composition comprising (i) an ethylene-based polymer and (ii) a bond having structure (2)

[0006]

[0007] The coating is formed from starting materials ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. The method includes heating the coating to a reprocessing temperature and forming the coating into a reprocessable ethylene polymer composition at the reprocessing temperature. The method includes forming the reprocessable ethylene polymer composition into a reprocessable preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked ethylene polymer composition, the recrosslinked ethylene polymer composition composed of (i) an ethylene polymer and (ii) a bond having structure (2). BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a perspective view of a sheet of three-dimensional random loop material according to an embodiment of the present disclosure.

[0009] Figure 1A yes Figure 1 An enlarged perspective view of area 1A.

[0010] Figure 2 is a table showing a top view photograph of each compression molded disc sample of Examples CS-1, IE-A, IE-B, IE-C, and IE-D after compression at 125°C for 22 hours at 25% strain.

[0011] definition

[0012] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).

[0013] The numerical range disclosed herein includes all values ​​from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values ​​(e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values ​​is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0014] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0015] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0016] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent listing any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.

[0017] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), ethylene / α-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or multiple reactor configurations.

[0018] "Ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin interpolymer containing a homogeneous short chain branching distribution, which comprises units derived from ethylene and units derived from at least one C3-C 10The ethylene plastomers / elastomers have a density of 0.854 g / cc to 0.917 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Polyolefin plastomers and ENGAGE TM Polyolefin elastomer (available from The Dow Chemical Company), EXACT TM Plastomers (available from Exxon Mobil Chemical), Tafmer TM α-olefin copolymer (available from Mitsui), Solumer TM Polyolefin Elastomers and Supreme TM Polyolefin plastomers (available from SK Chemicals Co.) and Lucene TM Polyolefin elastomer (available from LG Chem Ltd.).

[0019] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C 10 The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM(available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.

[0020] "Linear low density polyethylene" (or "LLDPE") is a linear ethylene / α-olefin copolymer containing a homogeneous or heterogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include ELITE TM Enhanced polyethylene resin, TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).

[0021] "Low density polyethylene" (or "LDPE") is a homopolymer of ethylene or a polyolefin having a density of 0.915 g / cc to less than 0.940 g / cc. 10 LDPE is composed of ethylene / α-olefin copolymers of C4-C8 α-olefins and contains long chain branching with a broad molecular weight distribution. LDPE is usually produced by high pressure free radical polymerization (tubular reactor or autoclave with free radical initiator). Non-limiting examples of LDPE include AGILITY TM Performance LDPE and DOW TM LDPE (available from Dow Chemical Company), MarFlex TM (Chevron Phillips), LUPOLEN TM (LyondellBasell) as well as LDPE products from Borealis, INEOS, ExxonMobil and others.

[0022] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers and propylene polymers.

[0023] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.

[0024] Test Method

[0025] Apparent density The sample material was cut into square pieces measuring 38 cm x 38 cm (15 in x 15 in). The volume of this piece was calculated from the thickness measured at four points. The weight was divided by the volume to give the apparent density (taking the average of the four measurements), which is reported in grams per cubic centimeter, g / cc.

[0026] Compression set Compression set was measured according to ASTM D395 Method B at 25% strain for 22 hours (hr) at 70°C using one specimen per sample.

[0027] density Measured according to ASTM D792, Method B using isopropyl alcohol and results are reported in g / cc at 25°C.

[0028] Rheological properties analysisUse rubber processing analyzer (RPA). According to ASTM D6204, the rheological properties of the composition were measured using a rotorless oscillating shear rheometer Alpha Technologies RPA 2000 instrument under the following test conditions and exceptions. The sample was placed between two polyester films for analysis. During the initial timing test, the rheological properties were monitored for 60 min at 160 ° C, 1.0 rad / s, 7% strain. The elastic torque S' at the end of the 60 min crosslinking step was recorded. After 60 min at 160 ° C, the same sample was immediately subjected to a frequency sweep of 0.1 rad / s to 300 rad / s at 160 ° C, 7% strain, then a frequency sweep of 0.1 rad / s to 300 rad / s was carried out at 190 ° C, 7% strain, and then a frequency sweep of 0.1 rad / s to 300 rad / s was carried out at 230 ° C, 7% strain. The dynamic complex viscosity, n* and tan δ of each frequency sweep were recorded. In ASTM D6204, a frequency sweep was carried out on unvulcanized rubber before the curing step. In this case, a frequency sweep was performed after an initial cross-linking step at 160 °C to evaluate the reversibility of the cross-linking.

[0029] Melt Index (MI or I2) (for ethylene-based polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, wherein the results are reported in grams per 10 minutes (g / 10 min).

[0030] Wire debonding force . The samples were prepared by extruding wires on an Xplore MC 40 micro mixer ("MC 40") and collecting the curled wires. 20 g samples were processed on the MC 40. The temperature was set to 200 ° C for all runs. The screw speed was initially set to 25 rpm. Approximately 10 g of sample was added to the MC 40 and allowed to melt for about 30 s. Then, another 10 g of sample was added. The screw speed was increased to 50 rpm. Then, the material was recirculated in the micro mixer for 5 min, at which time a stable torque reading was obtained. A single extrudate wire with a diameter of approximately 4 mm was then extruded from the micro mixer. The extruded wires were collected on a Teflon sheet approximately 6 inches from the die outlet and manually moved to collect the curled wires, where the extrudates curled themselves to form a joint, repeating the 3D ring extrusion and bonding process. The curled wires were cooled to room temperature. The strength of the wire joints was evaluated by cutting a single bonding joint from the curled wire and evaluating it under uniaxial tension on an Instron test frame. The samples were tested at room temperature with a crosshead displacement speed of 5 inches / minute. The peak load that caused the wire to break or debond the wire at the joint was recorded. The average peak load of 3 to 5 specimens per sample was reported. DETAILED DESCRIPTION

[0031] The present disclosure is an article. The article is composed of a three-dimensional random ring material (or "3DRLM"). The 3DRLM includes a mesh structure of multiple curved continuous wires melt-bonded together at multiple contact points to form multiple rings. Each continuous wire is composed of a cross-linked polymer composition, which is formed by a starting material comprising (i) an ethylene polymer and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).

[0032] A.3DRLM

[0033] The present disclosure relates to articles composed of three-dimensional random ring materials (or "3DRLM"). For illustrative purposes, Figure 1 A sheet 10 consisting of a three-dimensional random ring material 30 is shown. It should be understood that the 3DRLM can be present in a variety of different shapes and is not limited to a sheet. The sheet 10 has a geometric shape. As used herein, a "geometric shape" is a three-dimensional shape or a three-dimensional configuration having a length, a width, and a height. The geometric shape can be a regular three-dimensional shape, an irregular three-dimensional shape, and a combination thereof. Non-limiting examples of regular three-dimensional shapes include cubes, prisms, spheres, cones, and cylinders. The sheet can be solid or hollow. It is understood that when the geometric shape of the sheet is a prism, the cross-sectional shape of the prism can be a regular polygon or an irregular polygon with three, four, five, six, seven, eight, nine, 10 or more faces. It should also be understood that when the geometric shape of the sheet is a cylinder, the cylinder can have an elliptical or circular cross-sectional shape.

[0034] The sheet 10 is composed of three-dimensional random ring material 30. Figure 1A As shown, a "three-dimensional random ring material" (or "3DRLM") is a mass or structure of many rings 32 formed by winding a continuous wire 34 to allow the corresponding rings to contact each other in a molten state and heat-bond or otherwise melt-bond at the contact points 36. Even when a large pressure that causes significant deformation is applied, the 3DRLM 30 absorbs the stress of the entire network structure composed of molten integrated three-dimensional random rings by deforming itself; and once the pressure is released, the elastic rebound of the polymer emerges to restore it to the original shape of the structure. When a network structure composed of continuous wires made of known non-elastic polymers is used as a cushioning material, plastic deformation occurs and recovery cannot be achieved, resulting in poor durability. When the wires are not melt-bonded at the contact points, the shape cannot be maintained and the structure does not change its shape as a whole, resulting in fatigue due to stress concentration, thereby reducing durability and deformation resistance. In certain embodiments, melt bonding is a state in which all contact points are melt-bonded.

[0035] A non-limiting method for producing 3DRLM 30 includes the following steps: (a) heating a molten olefin polymer (ethylene polymer, BiTEMPS methacrylate, free radical initiator) at a temperature 10°C to 140°C higher than the polymer melting point and / or glass transition temperature in a typical melt extruder; (b) discharging the molten interpolymer in a downward direction from a die having a plurality of orifices to form a continuous strand that falls naturally (due to gravity); contacting the extruded strand in a fluid (e.g., a water bath) below the crystallization temperature of the polymer so that the strand forms a ring when solidified. The polymer may be used in combination with a thermoplastic elastomer, a thermoplastic non-elastic polymer, or a combination thereof. The distance between the die surface and the output conveyor mounted on the cooling unit for solidifying the strand, the melt viscosity of the polymer, the diameter of the orifice, and the discharge volume are factors that determine the ring diameter and diameter of the strand. The ring is formed by holding and allowing the delivered molten wire to exist between a pair of output conveyors (belts or rollers) arranged on a cooling unit (the distance between them is adjustable), so that the rings thus formed are contacted with each other for this purpose by adjusting the distance between the orifices, so that the rings in contact are thermally bonded or otherwise melt-bonded when they form a three-dimensional random ring structure. Then, the continuous wire whose contact points have been thermally bonded when the rings form a three-dimensional random ring structure is continuously entered into a cooling unit for solidification to obtain a mesh structure. Thereafter, the structure is cut into the desired length and shape. The method is characterized in that the olefin polymer is melted and heated at a temperature 10°C-140°C higher than the melting point of the interpolymer, and is delivered in a molten state in a downward direction from a die having a plurality of orifices. When the polymer is discharged at a temperature less than 10°C higher than the melting point, the delivered wire becomes cold and less fluid, resulting in insufficient thermal bonding of the contact points of the wire.

[0036] The characteristics (such as ring diameter and diameter) of the wire material constituting the buffer mesh structure provided herein depend on the distance between the die surface and the output conveyor installed on the cooling unit for solidifying the interpolymer, the speed of the output conveyor, the melt viscosity of the interpolymer, the diameter of the orifice and the amount of the interpolymer to be delivered therefrom. For example, the amount of the interpolymer to be delivered is reduced and the melt viscosity is reduced, and the distance between the die and the conveyor is increased and the conveyor speed is increased during delivery, resulting in a smaller diameter of the wire material and a smaller average ring diameter of the random ring. On the contrary, the distance between the die surface and the output conveyor installed on the cooling unit for solidifying the interpolymer is shortened, resulting in a slightly larger diameter of the wire material and a larger average ring diameter of the random ring. The orifice diameter also affects the wire diameter and the ring diameter. A lower orifice diameter produces a wire material with a lower diameter and a smaller ring diameter. A larger orifice diameter produces a larger wire diameter and a larger ring diameter. These conditions combine to obtain the desired diameter of the continuous wire of 0.1mm to 4mm, and the average diameter of the random ring of no more than 100mm, or 1 millimeter (mm), or 2mm, or 10mm to 25mm, or 50mm.By adjusting the distance from the aforementioned conveyor, the thickness of the structure can be controlled while the thermal bonding network structure is in a molten state, and the structure conveyor speed with the desired thickness and the flat surface formed by the conveyor can be obtained. It is too large to cause the thermal bonding contact point, because cooling is carried out before thermal bonding.On the other hand, speed is too slow to cause the higher density caused by the excessively long stay of molten material.In some embodiments, the distance from the conveyor and the conveyor speed should be selected so that the desired apparent density of 0.005-0.1g / cc or 0.01-0.05g / cc can be achieved.

[0037] The 3DRLM 30 is formed into a three-dimensional geometric shape to form a sheet (i.e., a prism). The 3DRLM 30 is an elastic material that can be compressed and stretched and return to its original geometric shape. As used herein, an "elastic material" is a rubber-like material that can be compressed and / or stretched and expands / retracts very quickly to approximately its original shape / length when the force applying the compression and / or stretching is released. When no compressive force and no stretching force are applied to the 3DRLM 30, the three-dimensional random ring material 30 has a "neutral state". When a compressive force is applied to the 3DRLM 30, the three-dimensional random ring material 30 has a "compressed state". When an extension force is applied to the 3DRLM 30, the three-dimensional random ring material 30 has a "stretched state".

[0038] B. Ethylene polymers

[0039] The 3DRLM is formed from a crosslinkable polymer composition (interchangeably referred to as a "starting material") comprising an ethylene-based polymer. The ethylene-based polymer may be an ethylene homopolymer, an ethylene / α-olefin interpolymer, or an ethylene / C4-C 20Alpha-olefin copolymers. In embodiments herein, ethylenes include more than 50% by weight of units derived from ethylene and less than 30% by weight of units derived from one or more alpha-olefin comonomers (based on the total amount of polymerizable monomers). All individual values ​​and subranges of units derived from ethylene greater than 50% by weight and less than 30% by weight of units derived from one or more alpha-olefin comonomers. Suitable alpha-olefin comonomers generally have no more than 20 carbon atoms. For example, alpha-olefin comonomers may have 3 to 10 carbon atoms or 3 to 8 carbon atoms. Exemplary alpha-olefin comonomers include, but are not limited to, propylene 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene and 4-methyl-1-pentene. The one or more α-olefin comonomers may, for example, be selected from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-hexene and 1-octene. In some embodiments, the ethylene-based polymer comprises greater than 0 wt % and less than 30 wt % of units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.

[0040] The melt index (MI) of the ethylene polymer is from 0.1 g / 10min to 100 g / 10min, or from 1 g / 10min to 100 g / 10min, or from 1 g / 10min to 50 g / 10min, or from 1 g / 10min to 25 g / 10min, or from 1 g / 10min to 10 g / 10min, or from 1 g / 10min to 5 g / 10min. In embodiments herein, the density of the ethylene polymer is in the range of from 0.860 g / cc to 0.925 g / cc. All individual values ​​and subranges from 0.860 to 0.925 g / cc are included and disclosed herein. In some embodiments, the density of the ethylene composition may be 0.895 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.900 g / cc to 0.920 g / cc, 0.900 g / cc to 0.915 g / cc, 0.900 g / cc to 0.912 g / cc, 0.900 g / cc to 0.911 g / cc, or 0.900 g / cc to 0.910 g / cc. In other specific embodiments, the density of the ethylene polymer composition may be 0.875 g / cc to 0.925 g / cc, 0.890 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.903 g / cc to 0.925 g / cc, or 0.905 g / cc to 0.925 g / cc. Density can be measured according to ASTM D792.

[0041] Non-limiting examples of suitable ethylene-based polymers include ethylene / α-olefin interpolymers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and combinations thereof.

[0042] In one embodiment, the ethylene-based polymer is LLDPE.

[0043] In one embodiment, the ethylene / α-olefin interpolymer is an ethylene / C4-C8 α-olefin copolymer having one, some or all of the following characteristics:

[0044] (i) octene comonomer; and / or

[0045] (ii) a density of 0.860 g / cc to 0.925 g / cc, or 0.880 g / cc to 0.920 g / cc, or 0.899 g / cc to 0.915 g / cc, or 0.899 g / cc to 0.910 g / cc; and / or

[0046] (iii) a melt index of 0.5 g / 10 min to 100 g / 10 min, or 1 g / 10 min to 30 g / 10 min, or 2 g / 10 min to 20 g / 10 min. Suitable ethylene / C 4- Non-limiting examples of C8 alpha-olefin copolymers include ENGAGE TM 8450POE、ENGAGE TM 8402POE,

[0047] ENGAGE TM 8401POE、ELITE TM 5815 enhanced polyethylene resin, ELITE TM

[0048] 5220 enhanced polyethylene resin or their blends.

[0049] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to an ethylene / C3-C8 α-olefin multi-block copolymer composed of ethylene and a copolymerizable C3-C8 α-olefin comonomer or C4-C8 α-olefin comonomer (and optional additives) in polymerized form, the polymer being characterized in that multiple blocks or segments of two polymerized monomer units are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer comprising chemically distinguishable units connected end-to-end relative to the polymerized ethylenic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers having two blocks (diblocks) and more than two blocks (multiblocks). C3-C8 α-olefins are selected from propylene, butene, hexene and octene. The ethylene / α-olefin multi-block copolymer does not contain or otherwise does not contain styrene (i.e., does not contain styrene), and / or ethylene aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in a copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer may be represented by the formula: (AB) n ; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.

[0050] In one embodiment, ethylene constitutes the majority of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene constitutes at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene constitutes at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C3-C8 α-olefin comonomers or C4-C8 α-olefin comonomers. In one embodiment, the ethylene / α-olefin multi-block copolymer contains 50% to 90% by weight of ethylene, or 60% to 85% by weight of ethylene, or 65% to 80% by weight of ethylene.

[0051] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.

[0052] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.

[0053] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of polymer products with improved and distinguishable physical properties. The theoretical benefits of polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review E ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 The theoretical benefits of polydisperse block distributions are modeled and discussed in (1997) 107(21), pp. 9234-9238.

[0054] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.

[0055] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some or all of the following characteristics:

[0056] (i) an Mw / Mn of from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or

[0057] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or

[0058] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or

[0059] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or

[0060] (v) 50 wt% to 85 wt% of soft segments and 50 wt% to 15 wt% of hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or

[0061] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segment; and / or

[0062] (vii) 0.5 mol%, or 1.0 mol%, or 2.0 mol%, or 3.0 mol% to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene in the hard segments; and / or

[0063] (viii) 300% min at 21°C as measured according to ASTM D 1708 ·1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and / or

[0064] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).

[0065] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TM Olefin block copolymers are commercially available from The Dow Chemical Company, Midland, Michigan, USA.

[0066] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but especially in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.

[0067] C. Free Radical Initiator

[0068] The crosslinkable polymer composition forming the 3DRLM includes a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.

[0069] In one embodiment, the free radical initiator is dicumyl peroxide.

[0070] D.BiTEMPS Methacrylate

[0071] The crosslinkable polymer composition forming the 3DRLM comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, which is interchangeably referred to as “BiTEMPS methacrylate” or “BiTEMPS” or “BiT.” BiTEMPS methacrylate disulfide has the following structure 1.

[0072] Structure 1

[0073]

[0074] In one embodiment, the crosslinkable polymer composition comprises:

[0075] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of an ethylene polymer;

[0076] 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt %, 0.1 wt % to 3.0 wt %, or 0.1 wt % to 1.5 wt %, or 0.5 wt % to 1.5 wt % of a free radical initiator, which is an organic peroxide (e.g., dicumyl peroxide); and

[0077] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 2 wt % to 20 wt %, or 2 wt % to 10 wt % BiTEMPS methacrylate disulfide. It is understood that the aggregate of the vinyl polymer, free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.

[0078] The cross-linked composition of the continuous wire for 3DRLM is formed by a cross-linkable polymer composition. The cross-linkable polymer composition is melt blended at a temperature of 100°C to 250°C, or to 120°C to 210°C, or 140°C to 210°C, or 140°C to 190°C to trigger a cross-linking reaction and form a cross-linked composition. In one embodiment, the cross-linked composition comprises an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The cross-linked composition contains a disulfide bond formed by BiTEMPS methacrylate through a cross-linking reaction, and the disulfide bond has the following structure 2.

[0079] Structure 2

[0080]

[0081] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized ethylene (and optional comonomers) of the ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having an MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein. Non-limiting examples of suitable ethylene polymers include ethylene / α-olefin interpolymers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and combinations thereof.

[0082] In one embodiment, the vinyl polymer is a virgin vinyl polymer. As used herein, a "virgin vinyl polymer" is a vinyl polymer that has not been subjected to a crosslinking reaction. In other words, the term "virgin vinyl polymer" refers to the vinyl polymer that is present in the crosslinked composition before the vinyl polymer is crosslinked with the BiTEMPS methacrylate. The virgin vinyl polymer is the vinyl polymer prior to crosslinking, and the crosslinked composition contains the same vinyl polymer that is virgin but now crosslinked with the BiTEMPS methacrylate. In this way, the virgin vinyl polymer is used as a benchmark for evaluating the properties of the crosslinked composition. The crosslinked composition has

[0083] (i) a storage modulus value G' at 140°C that is greater than the storage modulus value G' of the virgin ethylene polymer at 140°C;

[0084] (ii) a tan δ value at 60°C that is less than the tan δ value at 60°C of the virgin ethylene polymer; and

[0085] (iii) a tan δ value at 140°C that is less than the tan δ value of the virgin ethylene polymer at 140°C,

[0086] And formed in 3DRLM as disclosed above.

[0087] In one embodiment, the crosslinked composition comprises 80 wt% to 99.9 wt% or 80 wt% to 98 wt% of an ethylene-based polymer and (ii) bonds of structure (2) formed from 2 wt% to 20 wt% BiTEMPS methacrylate, the aggregate of the ethylene-based polymer and bonds of structure (2) (formed from BiTEMPS methacrylate) (and optional additives) totaling 100 wt% of the crosslinked composition. The crosslinked composition in the wire of 3DRLM has

[0088] (i) a storage modulus value G' greater than 1 MPa at 60°C;

[0089] (ii) a storage modulus value G' at 140°C greater than 0.1 MPa;

[0090] (iii) a tan delta value of less than 0.17 at 60°C; and

[0091] (iv) a tan δ value of less than 0.62 at 140°C.

[0092] E. Blend Components

[0093] In one embodiment, the crosslinkable polymer composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include ethylene vinyl acetate (EVA), polyolefins (e.g., polyethylene other than the vinyl polymer crosslinked with BiTEMPS methacrylate and polypropylene), additional "virgin vinyl polymers" (e.g., the same vinyl polymer used in the crosslinked composition but not reacted or crosslinked with BiTEMPS methacrylate), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.

[0094] In one embodiment, the polyolefin is a homopolymer such as polyethylene, polypropylene, polybutene, polypentene-1, poly-3-methylbutene-1, poly-4-methylpentene-1, polyisoprene, polybutadiene, poly-1,5-hexadiene, polyhexene-1, polyoctene-1, and polydecene-1.

[0095] Non-limiting examples of polyethylenes suitable as blend components (other than ethylene polymers crosslinked with BITEMPS methacrylate) include ultra-low density polyethylene (ULDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high molecular weight high density polyethylene (HMW-HDPE), ultra-high molecular weight polyethylene (UHMW-PE), and combinations thereof. Non-limiting examples of polypropylenes include low density polypropylene (LDPP), high density polypropylene (HDPP), high melt strength polypropylene (HMS-PP), and combinations thereof. In one embodiment, the blend component is high melt strength polypropylene (HMS-PP), low density polyethylene (LDPE), or a combination thereof. Such commercially available LDPE or LLDPE is marketed under the trade name DOWLEX TM , DNDA and ATTANE TM , all of which are available from The Dow Chemical Company, Midland, Michigan.

[0096] F. Additives

[0097] The crosslinkable polymer composition and / or the crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of the additive may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.

[0098] G. Methods

[0099] BiTEMPS methacrylate is a "dynamic crosslinker." The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network of ethylene polymers through disulfide bonds between chains of the ethylene polymer. The crosslinked network is formed by the ethylene polymer and BiTEMPS methacrylate in the presence of a free radical initiator to form a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken, allowing the chains to move and exchange, when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature," which is a temperature of 160°C to 230°C or 160°C to 200°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.

[0100] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking into a new article can be repeated.

[0101] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing). For reprocessable, crosslinked ethylene polymer compositions, the ratio of the viscosity after reprocessing to the viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.

[0102] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.

[0103] The present disclosure provides a method. In one embodiment, the method comprises:

[0104] The first product is heated to a reprocessing temperature. The first product is composed of a three-dimensional random ring material, which is a mesh structure of multiple curved continuous wires that are melt-bonded together at multiple contact points to form multiple rings. Each continuous wire is composed of a cross-linked composition comprising a bond (and optional additives) of an ethylene polymer and structure 2 (formed by 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate). The method includes forming the first product into a reprocessable ethylene polymer composition at a reprocessing temperature. The method includes forming the reprocessable ethylene composition into a reprocessed preform at a reprocessing temperature. The method includes cooling the reprocessed preform to a second product composed of a recrosslinked ethylene polymer composition that is lower than the reprocessing temperature and forming the recrosslinked ethylene polymer composition, which is composed of (i) an ethylene polymer and (ii) a structure 2 (formed by BiTEMPS methacrylate).

[0105] The second article may be the same as or different from the first article.

[0106] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.

[0107] Non-limiting examples of suitable second articles for the re-crosslinked (reprocessed) ethylene polymer (with BiTEMPS methacrylate) compositions of the present invention include 3DL articles; elastic films; elastic fibers; soft touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and extruded profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather stripping; lid linings; flooring; and combinations thereof.

[0108] The applicant has discovered a 3DRLM that can undergo reversible crosslinking at reprocessing temperatures. This is achieved by forming a 3DRLM from a crosslinkable polymer composition of an ethylene polymer, a peroxide, and BITEMPS methacrylic acid (and optional additives). The composition of the present invention forms a 3DRLM with a wire composed of a crosslinked composition, wherein the crosslinked composition is crosslinked at the application use temperature, but can be melt-reprocessed at a typical 3DRLM processing temperature (about 160°C-230°C). Therefore, it is expected that the proposed solution provides benefits in terms of heat resistance and durability for 3DRLM ring liners while maintaining (re)processability at typical extrusion temperatures.

[0109] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.

[0110] 1. Materials

[0111] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.

[0112] Table 1 - Materials used in the Inventive Examples ("IE") and Comparative Samples ("CS")

[0113]

[0114] 2. Synthesis of BITEMPS Methacrylate

[0115] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (90 mL, provided by Sigma-Aldrich, dried on molecular sieves for 48 hr before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hr to obtain BiTEMPS methacrylate as shown in the following structure 1.

[0116] Structure 1

[0117]

[0118] 3. Preparation

[0119] ENGAGE 8450, dicumyl peroxide, and BiTEMPS methacrylate (in the amounts shown in Table 2 below) were combined and batch mixed at 100°C to form a crosslinkable polymer composition, Formulation A. Formulation A was heated on an RPA at 160°C for 60 minutes (min) to initiate the crosslinking reaction. The properties of the crosslinked composition are provided in Table 2 below.

[0120] Table 2: Formulation and properties

[0121] Component / PHR Preparation 1 Preparation A ENGAGE 8450 100 100 Dicumyl peroxide 1 BITEMPS Methacrylate 5 RPA S' at 160℃, 60min (dNm) 1.68 RPA n* at 0.1rad / s, 160℃ (Pa-s) 947,253 RPA n* at 300rad / s, 160℃ (Pa-s) 1,222 RPA tanδ at 0.1rad / s, 160℃ 0.42 RPA n* at 0.1rad / s, 230℃ (Pa-s) 54,258 RPA n* at 300rad / s, 230℃ (Pa-s) 459 RPA tanδ at 0.1rad / s, 230℃ 1.31 Viscosity Temperature Reprocessing Ratio 17.5 Reprocessable yes yes

[0122] The viscosity temperature reprocessing ratio is defined as the ratio of n* at 0.1 rad / s, 160°C to n* at 0.1 rad / s, 230°C. The S' at 160°C for 60 minutes and n* at 0.1 rad / s, 160°C indicate that Formulation A has undergone a crosslinking reaction. The significant decrease in n* at 0.1 rad / s, 230°C (high viscosity temperature reprocessing ratio) indicates that the crosslinked composition can be reprocessed at this elevated temperature. Formulation 1 is thermoplastic and has no crosslinking, so it is inherently reprocessable.

[0123] Samples were prepared by extruding wires and collecting curled wires on an Xplore MC 40 micro mixer ("MC 40"). 20 g samples were processed on MC 40. The temperature was set to 200 ° C for all runs. Initially, the screw speed was set to 25 rpm. About 10 g of sample was added to MC 40 and melted for about 30 seconds (s). Then, another 10 g of sample was added. The screw speed was increased to 50 rpm. Then, the material was recirculated in the micro mixer for 5 min, and a stable torque reading was obtained at this time, as recorded in Table 3 below. A single extrudate wire of about 4 mm in diameter was then extruded from the micro mixer. The extruded wire was collected on a Teflon sheet about 6 inches from the die outlet and manually moved to collect the curled wire, where the extrudate curled itself to form a junction, repeating the 3D ring extrusion and bonding process. The curled wire was cooled to room temperature.

[0124] Table 3: Extrusion samples

[0125] Example CS-1 IE-B IE-C IE-D Composition Preparation 1 IE-A 50 wt% Formulation 1 + 50 wt% IE-A Preparation A Micro mixer torque, Nm 16 28 20 23 Extruded wire diameter, mm 3.8 3.7 3.8 3.7 Wire Debonding Peak Load, lbf 22.1 3.7 9.9 3.8

[0126] The strength of the wire joints was evaluated by cutting individual bonded joints from the coiled wire and evaluating them on an Instron test frame under uniaxial tension. The peak loads of 3 to 5 specimens of each sample were measured as reported in Table 3 (above). For the comparative sample (CS1) made with a conventional thermoplastic ethylene / octene copolymer (ENGAGE 8450), most of the wires broke before debonding at the joint occurred.

[0127] For the inventive examples composed of reversibly crosslinked compositions (IE-B, IE-C, IE-D), the wires debonded at the joints at the reported wire debonding peak loads (Table 3 above). Although the peak loads for debonding of IE-B, IE-C, and IE-D were lower than that of comparative sample CS-1, each of the inventive examples of IE-B, IE-C, and IE-D had a measurable debonding force, indicating that adhesion did occur between the extruded wires and that articles similar to 3DRLM can be formed from reversibly crosslinked compositions.

[0128] For IE-D, a sample was formed using a crosslinkable polymer composition formulation A, demonstrating that the crosslinkable polymer composition can be easily processed into a final product, i.e., an extruded product comparable to a 3DRLM product, in which reversible crosslinking is established. Inventive Examples IE-B to IE-D were made using Inventive Example IE-A. Formulation A was crosslinked to form IE-A by compression molding into a plate (10 cm×10 cm×2 mm) at 180°C for 15 min. IE-A was then cut into small pieces for extrusion experiments on an Xplore MC 40 micro mixer. Examples IE-B and IE-C demonstrate that due to the reversible nature of crosslinking at processing temperature, the crosslinked material IE-A can be melt (re) processed into a new product (comparable to a 3DRLM product). Therefore, each of Inventive Examples IE-B, IE-C, and IE-D demonstrates the ability of a 3DRLM composed of an ethylene / octene copolymer crosslinked with BiTEMPS methacrylate to be melt processed and / or melt reprocessed.

[0129] In addition, to demonstrate the improved heat resistance of the crosslinked IE-B, IE-C and IE-D embodiments, the extruded wires were reprocessed to form compression molded discs for compression set testing. The wires were cut into pieces and compression molded into 1.2 inch diameter, 0.5 inch thick discs at 180°C for 15min. First, the compression set at 70°C was evaluated, as reported in Table 4. IE-B, IE-C and IE-D had similar compression set to the non-crosslinked CS-1 embodiment, demonstrating that the reversibly crosslinked composition maintained similar physical properties at 70°C. Each compression set disc of CS-1, IE-B, IE-C and IE-D was then reprocessed by compression molding to form a new 1.2 inch diameter, 0.5 inch thick disc by compression molding at 180°C for 15min. In addition, the compression molded plaque of IE-A was also compression molded into compression set discs. Each sample was then compressed at 125°C for 22 hr at 25% strain and then allowed to cool to room temperature. Figure 2 A photograph of a top view of each compression set disk after compression at 125°C for 22 hrs, 25% strain is shown. CS-1 melts and deforms when 125°C is above the melting point of the sample, and it is not cross-linked. Meanwhile, IE-A, IE-B, IE-C, and IE-D all retain their shapes, demonstrating the improved heat resistance of these cross-linked samples.

[0130] Table 4 - Compression set

[0131] Compression set (22hr, 70℃)% CS-1 61 IE-A -- IE-B 65 IE-C 63 IE-D 67

[0132] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.

Claims

1. A product comprising: a three-dimensional random loop material comprising a network of a plurality of curved continuous wires melt-bonded together at a plurality of contact points to form a plurality of loops; Each continuous strand is comprised of a cross-linked composition formed from a starting material comprising: Ethylene polymers; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).

2. The article of claim 1, wherein the crosslinked composition comprises a bond of structure 2 3. The article according to any one of claims 1 to 2, wherein the cross-linked composition is formed from a starting material comprising: 80 to 99 weight percent of an ethylene polymer having a melt index of 0.1 to 100 g / 10 min; and 20 wt % to 1 wt % of said BiTEMPS methacrylate.

4. The article of any one of claims 1 to 3, wherein the ethylene-based polymer is an ethylene / α-olefin interpolymer having a density from 0.860 g / cc to 0.925 g / cc.

5. The article of any one of claims 1 to 4, wherein the ethylene-based polymer is an ethylene / octene copolymer.

6. The article according to any one of claims 1 to 5, wherein The ethylene polymer is a virgin ethylene polymer prior to crosslinking the crosslinking composition; and The cross-linked composition has (i) a storage modulus value G' at 140°C, which is greater than the storage modulus value G' of the native ethylene polymer at 140°C; (ii) a tan δ value at 60°C that is less than the tan δ value at 60°C of the native ethylene polymer; and (iii) a tan δ value at 140°C that is less than the tan δ value of the native ethylene polymer at 140°C.

7. A product comprising: a three-dimensional random loop material comprising a network of a plurality of curved continuous wires melt-bonded together at a plurality of contact points to form a plurality of loops; Each continuous strand is composed of a cross-linked composition comprising: Ethylene polymers; as well as Bonds with structure 2 8. A method comprising: The first article is heated to a reprocessing temperature, the first article being comprised of a three-dimensional random loop material comprising a network of a plurality of sinuous continuous strands melt-bonded together at a plurality of contact points to form a plurality of loops, each continuous strand being comprised of a cross-linked composition comprising: (i) ethylene polymers, and (ii) A bond having structure (2) forming the first article into a reprocessable ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene composition into a reprocessable preform at the reprocessing temperature; as well as The reprocessed preform is cooled to below the reprocessing temperature and forms a second article comprised of a recrosslinked ethylene polymer composition comprised of (i) the ethylene polymer and (ii) bonds having the structure (2).